Talk or type? The effect of digital interfaces on citizens' satisfaction with standardized public services - Christine Prokop; Markus Tepe (Public Administration, 2021)
Although digital interfaces are increasingly pervading public administration, little is known about how replacing face-to-face interaction with digital interfaces affects citizens' satisfaction with public service encounters. This study presents evidence from a vignette experiment conducted on a sample of German citizens (N =0.167em1.234) whereby we randomly varied the type of public service request with regard to its psychological costs, service quality, and the type of interaction (face-to-face, self-service terminal, or app). We found that replacing face-to-face communication with a digital interface has no effect on citizens' satisfaction, nor does it mitigate the effect of psychological costs, service failure, and recovery. Corroborating previous research on service recovery, we found that explaining and apologizing partially compensates for failure. Based on these results, we conclude that using digital interfaces does not undermine the goal to enhance citizen satisfaction with public services.
Keywords: 340